2002
DOI: 10.1074/jbc.c200419200
|View full text |Cite
|
Sign up to set email alerts
|

Single Mutation (A162H) in Human Cardiac Troponin I Corrects Acid pH Sensitivity of Ca2+-regulated Actomyosin S1 ATPase

Abstract: In contrast to skeletal muscle, the efficiency of the contractile apparatus of cardiac tissue has long been known to be severely compromised by acid pH as in the ischemia of myocardial infarction and other cardiac my- 2؉ sensitivity of cardiac contractility at low pH ( Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(69 citation statements)
references
References 30 publications
1
68
0
Order By: Relevance
“…Sample Preparation-Uniformly deuterated cysteineless chicken fast skeletal muscle TnI was expressed and purified as described (24), using a construct provided by Dr. Smillie (26). Substitution of cysteineless TnI for wild-type TnI in the Tn complex does not alter the Ca 2ϩ -dependent regulation of myosin ATPase activity (26).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sample Preparation-Uniformly deuterated cysteineless chicken fast skeletal muscle TnI was expressed and purified as described (24), using a construct provided by Dr. Smillie (26). Substitution of cysteineless TnI for wild-type TnI in the Tn complex does not alter the Ca 2ϩ -dependent regulation of myosin ATPase activity (26).…”
Section: Methodsmentioning
confidence: 99%
“…Substitution of cysteineless TnI for wild-type TnI in the Tn complex does not alter the Ca 2ϩ -dependent regulation of myosin ATPase activity (26). A uniformly deuterated deletion mutant of chicken skeletal muscle TnT (isoform TnT-3), corresponding to the T2 domain, was expressed and purified as described (25).…”
Section: Methodsmentioning
confidence: 99%
“…An interesting aspect of the specialization of the cTnI isoform is an alanine at position 164 near the mobile domain, which is replaced by His at the homologous position in ssTnI. Dargis et al [39] reported that this substitution is of significance in studies in which reconstitution with the mutant, cTnI (A164H), rendered cardiac myofilament preparations relatively more sensitive to Ca 2+ and relatively less sensitive to deactivation by acidic pH. Incorporation of cTnI (A164H) into hearts of transgenic mice recapitulated many of the effects of ssTnI described above, while retaining phosphorylation sites [40].…”
Section: Molecular Mechanisms Of Ctni Function In Ca2+ and Crossbridgmentioning
confidence: 99%
“…23 There is evidence that a difference in a single amino acid (His/Ala) in ssTnI versus cTnI at position 162 is responsible for these functional differences. 24 …”
Section: Targeting Ctni-actin Interactionsmentioning
confidence: 99%